Pengenalan dan Pelatihan Algoritma Pemrograman Menggunakan Python untuk Siswa SMK Jurusan Teknik Komputer dan Jaringan - Mira Pedeng; Christian Cahyaningtyas; Tessa Januarti (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The rapid development of information and communication technology demands that Vocational High School (SMK) students, particularly those majoring in Computer and Network Engineering (TKJ), master basic programming skills and understand the concept of the Internet of Things (IoT). However, many students still struggle to systematically construct algorithmic logic and understand programming syntax. The Python language, known for its simple syntax, high flexibility, and broad community support, is a suitable alternative for introducing programming basics and practical IoT implementation. This community service activity aims to provide algorithm and programming training using Python, while introducing IoT concepts and practices to students of SMK Negeri 1 Bengkayang. The training was conducted in four stages: preparation, theoretical introduction, practical implementation, and evaluation. Evaluation was conducted with pre- and post-tests to measure the improvement in participants' understanding. The pre-test results showed an average score of 41.54 points, while the post-test increased to 66.67 points. In addition to the improved scores, participants also showed high enthusiasm and provided positive feedback on the interactive and hands-on training method. This activity has had a tangible impact on improving participants' digital literacy and technical skills, and provides an initial foundation for developing competencies in programming and IoT technology. This training also has the potential to be replicated in other schools as a technology-based applied learning model relevant to industry needs